Stations of the Publicum Portorium Illyrici are a Strong Predictor of the Mithraic Presence in the Danubian Provinces: Geographical Analysis of the Distribution of the Roman Cult of Mithras - Chalupa Aleš; Glomb Tomáš; Sarkisjan Juraj (Open Archaeology)
The article examines the relationship between the Roman cult of Mithras and members of the publicum portorium Illyrici, the Roman customs office active in the Danubian provinces, who have been discussed in previous research as potentially important carriers of this cult. To investigate this relationship and its extent, spatial proximity analysis is performed with respect to documented portorium stations and confirmed Mithraic finds. For comparative purposes, the spatial proximity between portorium stations and finds relating to other selected Graeco-Roman deities was also examined. On the basis of the results of this analysis, it is possible to conclude that Mithraic finds are located significantly closer to customs stations than those of other Graeco-Roman deities (with the exception of Jupiter, the main Graeco-Roman god) and that the presence of a portorium station strongly predicts the presence of a Mithraic cult at a given site or in its immediate vicinity, especially in the Western cluster of portorium provinces. Thus, in a nuanced form and using a quantitative method of geographical analysis, the study supports previous conclusions about the importance of portorium officials as a social group significantly involved in the spread of the Roman cult of Mithras in the Danubian provinces.